2021
DOI: 10.7554/elife.70504
|View full text |Cite
|
Sign up to set email alerts
|

Patched 1 reduces the accessibility of cholesterol in the outer leaflet of membranes

Abstract: A long-standing mystery in vertebrate Hedgehog signaling is how Patched 1 (PTCH1), the receptor for Hedgehog ligands, inhibits the activity of Smoothened, the protein that transmits the signal across the membrane. We previously proposed (Kinnebrew et al., 2019) that PTCH1 inhibits Smoothened by depleting accessible cholesterol from the ciliary membrane. To directly test the effect of PTCH1 on accessible cholesterol, we measured the transport activity of PTCH1 using an imaging-based assay to follow the kinetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 72 publications
2
56
0
Order By: Relevance
“…Our results suggest that constitutive cholesterol binding to the TMD site in SMO changes the energy landscape of SMO such that basal signaling activity is increased. The CRD provides a restraining influence, preventing full SMO activation, until SHH (by inactivating PTCH1) increases outer leaflet cholesterol accessibility to the point that the CRD site is occupied ( 4 ). This model explains the modest SHH responsiveness of mSMO-ΔCRD: An increase in cholesterol accessibility triggered by SHH will lead to greater occupancy of the TMD site and hence an increase in signaling activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results suggest that constitutive cholesterol binding to the TMD site in SMO changes the energy landscape of SMO such that basal signaling activity is increased. The CRD provides a restraining influence, preventing full SMO activation, until SHH (by inactivating PTCH1) increases outer leaflet cholesterol accessibility to the point that the CRD site is occupied ( 4 ). This model explains the modest SHH responsiveness of mSMO-ΔCRD: An increase in cholesterol accessibility triggered by SHH will lead to greater occupancy of the TMD site and hence an increase in signaling activity.…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of SHH, the abundance of cholesterol in the membrane leads to occupancy of the TMD site, driving basal signaling activity. However, PTCH1 uses its transporter activity to reduce accessible cholesterol in the outer leaflet of the ciliary membrane ( 2 , 4 ), ensuring that the CRD site remains unoccupied and, consequently, the CRD maintains its inhibitory restraint on the TMD. When PTCH1 is inactivated by SHH, cholesterol binds to the CRD because the concentration of accessible cholesterol in the outer leaflet of the membrane rises ( 4 ), driving full SMO activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, recent biochemical, structural and cell biological studies have demonstrated that cholesterol also acts as a second messenger to communicate HH signals between PTCH1 and SMO ( Table 2 ). PTCH1 could move cholesterol from the outer to the inner leaflet of the membrane in exchange for potassium ion export ( Kinnebrew et al, 2021 ). A study on the structural analysis of cholesterol-activated Xenopus laevis SMO (xSMO) indicated that cholesterol-mediated SMO activation is correlated with the rearrangement of CRD orientation and a cation-lock opening in the transmembrane domain (TMD) of SMO ( Huang et al, 2018 ).…”
Section: Requirement For Cholesterol In Hedgehog Pathway Transductionmentioning
confidence: 99%
“…Hh autoprocessing is important because it is at the origin of canonical Hh signaling, where it precedes all downstream signaling events ( Porter et al, 1996a ; Hall et al, 1997 ; Jiang and Paulus, 2010 ; Xie et al, 2014 ; Xie et al, 2015 ; Xie et al, 2016 ; Zhang et al, 2019 ; Zhao et al, 2019 ; Smith et al, 2020 ), and is unique to Hh proteins. Although it lies at the very origin of Hh signaling, there are only a few structural/mechanistic studies ( Owen et al, 2015a ; Owen et al, 2015b ; Callahan and Wang, 2015 ; Bordeau et al, 2016 ; Ciulla et al, 2018 ; Ciulla et al, 2019 ; Zhang et al, 2019 ; Zhao et al, 2019 ; Smith et al, 2020 ), compared to the great number of studies of downstream components, such as PTCH ( Ingham et al, 1991 ; Chen and Struhl, 1996 ; Sidransky, 1996 ; Kallassy et al, 1997 ; Xie et al, 1997 ; Zedan et al, 2001 ; Shao et al, 2006 ; Lorberbaum et al, 2016 ; Tukachinsky et al, 2016 ; Zhang et al, 2018 ; Abd Elrhman and Ebian, 2019 ; Kinnebrew et al, 2021 ), SMO ( Xie et al, 2014 ; Owen et al, 2015a ; Owen et al, 2015b ; Callahan and Wang, 2015 ; Xie et al, 2015 ; Xie et al, 2016 ; Zhang et al, 2019 ; Zhao et al, 2019 ; Smith et al, 2020 ), and GLI ( Lauth et al, 2007 ; Kim et al, 2010 ; Maun et al, 2010 ; Beauchamp et al, 2011 ; Pan et al, 2012 ; Long et al, 2016 ; Xiao et al, 2017 ; Kowatsch et al, 2019 ; Liu et al, 2019 ; Quaglio et al, 2020 ; Tran et al, 2020 ). In some context with direct cell-to-cell contact, the unprocessed full-length Hh protein is reported to have signalin...…”
Section: Introductionmentioning
confidence: 99%